2015
DOI: 10.1038/srep10423
|View full text |Cite
|
Sign up to set email alerts
|

Unique somatic and malignant expression patterns implicate PIWI-interacting RNAs in cancer-type specific biology

Abstract: Human PIWI-interacting RNAs (piRNAs) are known to be expressed in germline cells, functionally silencing LINEs and SINEs. Their expression patterns in somatic tissues are largely uncharted. We analyzed 6,260 human piRNA transcriptomes derived from non-malignant and tumour tissues from 11 organs. We discovered that only 273 of the 20,831 known piRNAs are expressed in somatic non-malignant tissues. However, expression patterns of these piRNAs were able to distinguish tissue-of-origin. A total of 522 piRNAs are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
171
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(181 citation statements)
references
References 75 publications
9
171
1
Order By: Relevance
“…In cancer tissues, aberrant expression of piRNAs implied by global hypomethylation and focal hypermethylation are probably potential cancer-specific signatures [72, 73]. Accumulating evidence has revealed that several piRNAs have been implicated in cancer development, though only a small number of piRNAs have been found to express in somatic tissues at present [74]. Martinez et al [74] analyzed 6, 260 human piRNA transcriptomes derived from non-malignant and tumor tissues from 11 organs and discovered that only 273 of the 20, 831 known piRNAs are expressed in somatic non-malignant tissues and 522 piRNAs are expressed in corresponding tumor tissues, with a cancer-type specific manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cancer tissues, aberrant expression of piRNAs implied by global hypomethylation and focal hypermethylation are probably potential cancer-specific signatures [72, 73]. Accumulating evidence has revealed that several piRNAs have been implicated in cancer development, though only a small number of piRNAs have been found to express in somatic tissues at present [74]. Martinez et al [74] analyzed 6, 260 human piRNA transcriptomes derived from non-malignant and tumor tissues from 11 organs and discovered that only 273 of the 20, 831 known piRNAs are expressed in somatic non-malignant tissues and 522 piRNAs are expressed in corresponding tumor tissues, with a cancer-type specific manner.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has revealed that several piRNAs have been implicated in cancer development, though only a small number of piRNAs have been found to express in somatic tissues at present [74]. Martinez et al [74] analyzed 6, 260 human piRNA transcriptomes derived from non-malignant and tumor tissues from 11 organs and discovered that only 273 of the 20, 831 known piRNAs are expressed in somatic non-malignant tissues and 522 piRNAs are expressed in corresponding tumor tissues, with a cancer-type specific manner. Altogether, piRNAs are involved in cancer cell proliferation, apoptosis, metastasis, invasion, and may be as potential prognostic and diagnostic biomarkers during cancer development (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…While initial studies have shown that HPV infection affects the expression of some small non-coding RNAs, such as miRNAs, its effect on piRNA expression is unknown. The association of piRNA with patient outcome has been previously demonstrated in other cancer types, such as breast and gastric, among others 16,17,19 . Thus, it is of great relevance to characterize changes in piRNA expression patterns in the context of HPV status, as these piRNAs may represent novel predictors of clinical outcome in HPV+ HNSCC.…”
Section: Discussionmentioning
confidence: 78%
“…A custom sequence analysis pipeline was developed to deduce piRNA expression from raw sequencing data (FASTQ files) 16 . Briefly, our pipeline includes sample accrual, quality control and data quantification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation